The Development of Prospective Teachers’ Entrepreneurial Competencies Based on Importance Performance Analysis (IPA) (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
This study aims to analyze prospective teachers’ map of competency development; the effectiveness of the substance of education in various fields of study that supports the strengthening of prospective teachers’ entrepreneurial competencies and skills (startup businesses) after graduation; and the suitability of students’ entrepreneurial competency development quadrant. Methodologically, this study used survey method. It involved 1.298 third and upper semester students of University of Mataram’s Faculty of Teacher Training and Education (FKIP), who were determined using accidental proportional sampling. The dimensions and the instruments of this research were adapted from the instruments developed by Bikse and Reimera, which include: ability to learn and act independently, set goals and act in a creative way, ability to analyze and plan further action, to take the initiative and responsibility, cooperate and work in a team, assess and classify the information, and find the problem and plan the solution. All data were analyzed using descriptive analysis and Importance Performance Analysis (IPA). The results of the study indicate that efforts to strengthen entrepreneurial competencies, especially in selecting, summarizing, and presenting informations, have been made. However, the skills required to take initiative and direct personal responsibility are still not sufficiently developed. The findings of this study also show that prospective teachers are not completely well-prepared for the challenges in the labor market. Prospective teachers acquired moderate or even low-level theoretical knowledge and practical skills. This is confirmed by the results of Importance Performance Analysis which demonstrate that the entrepreneurial competency development is yet to be optimal. Almost all aspects of entrepreneurial competency development fall within quadrant I.